2015
DOI: 10.1002/ajmg.a.37101
|View full text |Cite
|
Sign up to set email alerts
|

Refining the regulatory region upstream of SOX9 associated with 46,XX testicular disorders of Sex Development (DSD)

Abstract: Disorders of Sex Development (DSD) are a heterogeneous group of disorders affecting gonad and/or genito-urinary tract development and usually the endocrine-reproductive system. A genetic diagnosis is made in only around 20% of these cases. The genetic causes of 46,XX-SRY negative testicular DSD as well as ovotesticular DSD are poorly defined. Duplications involving a region located ∼600 kb upstream of SOX9, a key gene in testis development, were reported in several cases of 46,XX DSD. Recent studies have narro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…Mutations involving the human TESCO element have not been reported as a cause of DSD, however, rearrangements involving another regulatory element, termed RevSex , located 600 kb upstream of SOX9 , are associated with both XY and XX DSD. Five cases of 46,XX testicular or ovotesticular DSD that carried duplications of this region and a familial case of 46,XY DSD that carried a deletion of the element have been reported [Benko et al, 2011;Cox et al, 2011;Vetro et al, 2011;Hyon et al, 2015]. The minimal region associated with 46,XX-SRY negative DSD has been narrowed down to a 40.7-41.9-kb element, which contains 2 predicted enhancer motifs [Hyon et al, 2015].…”
Section: Sry and Sox9mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations involving the human TESCO element have not been reported as a cause of DSD, however, rearrangements involving another regulatory element, termed RevSex , located 600 kb upstream of SOX9 , are associated with both XY and XX DSD. Five cases of 46,XX testicular or ovotesticular DSD that carried duplications of this region and a familial case of 46,XY DSD that carried a deletion of the element have been reported [Benko et al, 2011;Cox et al, 2011;Vetro et al, 2011;Hyon et al, 2015]. The minimal region associated with 46,XX-SRY negative DSD has been narrowed down to a 40.7-41.9-kb element, which contains 2 predicted enhancer motifs [Hyon et al, 2015].…”
Section: Sry and Sox9mentioning
confidence: 99%
“…Five cases of 46,XX testicular or ovotesticular DSD that carried duplications of this region and a familial case of 46,XY DSD that carried a deletion of the element have been reported [Benko et al, 2011;Cox et al, 2011;Vetro et al, 2011;Hyon et al, 2015]. The minimal region associated with 46,XX-SRY negative DSD has been narrowed down to a 40.7-41.9-kb element, which contains 2 predicted enhancer motifs [Hyon et al, 2015]. There is also data suggesting that deletions of an immediately adjacent and non-overlapping region are associated with 46,XY gonadal dysgenesis [Kim et al, 2015].…”
Section: Sry and Sox9mentioning
confidence: 99%
“…It has been speculated that a deletion of this enhancer prevents upregulation of SOX9 and hence testis development in 46,XY individuals, while duplication in 46,XX patients elevates SOX9 to sufficiently high levels to override the ovarian pathway and drive the formation of (sterile) testes or ovotestes. The minimal overlap between all the patients identified has been used to define the RevSex region from 178 kb [Cox et al, 2011] to 96 kb [Vetro et al, 2011], 78 kb [Benko et al, 2011], 67 kb [Xiao et al, 2013], 41 kb [Hyon et al, 2015], and most recently to 24 kb which should contain testis specific SOX9 enhancer(s) .…”
Section: Cnvs Affecting Noncoding Regulatory Regions Of Genes Associamentioning
confidence: 99%
“…Two further cases with partially overlapping 17q24.3 duplications ∼ 500 kb upstream of SOX9 presented with dissimilar phenotypes: one was an infertile male with testes, while the other was an ovotesticular DSD with ambiguous genitalia [Vetro et al, 2015]. Finally, 3 recent reports [Xiao et al, 2013;Hyon et al, 2015;Kim et al, 2015] have identified 7 further SRY -negative patients with 46,XX testicular or ovotesticular DSD, who carried duplications ranging from 68 to 83.8 kb, located ∼ 510-600 kb upstream of SOX9 , which overlapped with previously reported rearrangements and allowed refining the minimal region to a 40.7-41.9-kb element.…”
Section: Mechanisms Underlying Testis Differentiation In Sry -Negativmentioning
confidence: 99%